Variance in Call Duty and Hazard Allowances: Implication on Health Workers Commitment and Work Relations in Nigeria - Agba, A. M. Ogaboh; Etobe, Eteng I.; Titus, T. Charlie; Angioha, Pius U.; Ibioro, Francis E. (ACEND Foundation, 2021)
This study examines disparity in call duty and hazard allowance and its implication on health worker's commitment and industrial dispute in tertiary hospital in South-South, Nigeria. A survey method that allows for the use of structured questionnaire was adopted. The study used a combination of purposive and random sampling techniques in determining a sample of 1191 participants from 4 tertiary hospitals in South-South Nigeria. Data gathered from the field was coded and analyzed using Linear Regression at 0.05 level of significance. Results revealed that call duty discrepancies and hazard allowances significantly affect health workers' commitment and industrial disputes in tertiary hospitals. The study recommended, among others, that National Salaries, Incomes and Wages Commission should carry out a comprehensive review of all health worker's wages and allowances in Nigeria with the view of harmonizing them. The commission should also evolve a periodic pay reform for health workers in Nigeria.